2022
DOI: 10.3390/ani12212956
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing Reveals Pathways Related to Proliferation and Differentiation of Shitou Goose Myoblasts

Abstract: Chinese Shitou goose is a type of large goose with high meat yield. Understanding the genetic regulation of muscle development in Shitou goose would be beneficial to improve the meat production traits of geese. Muscle development is regulated by genes related to myoblast proliferation and differentiation. In this study, the RNA-seq method was used to construct the mRNA and lncRNA expression profiles of Shitou goose myoblasts and myotubes. A total of 1664 differentially expressed (DE) mRNAs and 244 DE-lncRNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
2
1
0
Order By: Relevance
“…A total of 1954 DEGs, 1479 AS, and 253 TFs were detected during the proliferation and differentiation of SMSCs. We found that the expression levels of all genes during proliferation were higher than those during the differentiation of SMSCs, which is consistent with the results of previous studies [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A total of 1954 DEGs, 1479 AS, and 253 TFs were detected during the proliferation and differentiation of SMSCs. We found that the expression levels of all genes during proliferation were higher than those during the differentiation of SMSCs, which is consistent with the results of previous studies [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The absence of satellite cells severely hampers myogenic differentiation during the initial wave of muscle regeneration [ 14 ]. Furthermore, studies have been reported on myoblast proliferation and differentiation study of the transcriptome of many species such as mice [ 15 , 16 ], geese [ 17 ], goats [ 18 ], and pigs [ 19 ], but there are few transcriptome studies involving ovine skeletal muscle satellite cells.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, variations in the cell type likely explain the differences in the results, as supported by our previous work, which identified a larger number of circRNAs in Shan Ma duck breast muscle tissues at different embryonic stages [1]. Comparative studies, such as the analysis conducted by Chen et al [19] in Shitou goose, reported a higher number of DE-lncRNAs than we observed in our study. Our results highlight the prevalence of intergenic lncRNAs and exonic circRNAs, which is in line with previous research [20,21].…”
Section: Discussionsupporting
confidence: 83%